ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR DI SAMSAT RUMBAI - Erliyana Fitrayanti; Meliza Putriyanti Zifi; Tobi Arfan (Jurusan Akuntansi Politeknik Negeri Bandung, 2018)
Abstract: This study aims to determine whether understanding of tax laws, quality of service, rational attitude, and perceptions of tax sanctions affect taxpayer compliance. The objects of the research are taxpayers who do not pay in SAMSAT-Rumbai. The population in this study was 2.054 vehicles whose does pay and samples in this study were 96 people consisting of 73 taxpayer two-wheeled vehicles and 23 taxpayer four-wheel vehicles. Analysis of the data in this study is taxpayer compliance as dependent variable while understanding of tax regulation, quality of service, rational attitude and perception of tax sanction as independent variables. Processing of the data in this study used SPSS 24 software where hypothesis testing used F-test (simultaneous). From the result of this study, it can be concluded that the variable of understanding of taxation regulation, quality of service, rational attitude and perception of tax sanction influenced simultaneously to tax compliance for two-wheeled and four-wheeled vehicles.Keywords: Taxation Regulation, Quality of Service, Rational Attitude, Tax Sanction, Taxpayer compliance.